TRANSFORMATION OF THE PRACTICE OF GIVING 'LIN WELIN LETO WOTER' IN KROWE ETHNIC MARRIAGES: ANALYSIS OF CAUSAL FACTORS AND COMMUNITY RESPONSE - Renhat Marlianus Siki; I Made Suastika; Maria Matildis Banda; Luh Putu Puspawati (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2024)
This research explores the transformation of the practice of giving